Magnetic Removal of Micro- and Nanoplastics from Water—from 100 nm to 100 µm Debris Size - Gaß, Henrik; Höfling, Anna; Müller, Lukas; Rockmann, Linda; Schubert, Dirk W.; Halik, Marcus; Kloos, Tonya (Small, 2023)
Clean water is one of the most important resources of the planet but human-made contamination with diverse pollutants increases continuously. Microplastics (<5 mm diameter) which can have severe impacts on the environment, are present worldwide. Degradation processes lead to nanoplastics (<1 µm), which are potentially even more dangerous due to their increased bioavailability. State-of-the-art wastewater treatment plants show a deficit in effectively eliminating micro- and nanoplastics (MNP) from water, particularly in the case of nanoplastics. In this work, the magnetic removal of three different MNP types across three orders of magnitude in size (100 nm–100 µm) is investigated systematically. Superparamagnetic iron oxide nanoparticles (SPIONs) tend to attract oppositely charged MNPs and form aggregates that can be easily collected by a magnet. It shows that especially the smallest fractions (100–300 nm) can be separated in ordinary high numbers (1013 mg−1 SPION) while the highest mass is removed for MNP between 2.5 and 5 µm. The universal trend for all three types of MNP can be fitted with a derived model, which can make predictions for optimizing SPIONs for specific size ranges in the futur

Remediation of charged organic pollutants—binding motifs for highly efficient water cleaning with nanoparticles - Eigen, Andreas; Schmidt, Victoria; Sarcletti, Marco; Freygang, Selina; Hartmann-Bausewein, Andreas; Schneider, Vanessa; Zehetmeier, Anna; Mauritz, Vincent; Müller, Lukas; Gaß, Henrik; Rockmann, Linda; Crisp, Ryan; et al. (Nano Select, 2023)
Many charged organic molecules behave as persistent and hazardous pollutants with harmful effects on human health and ecosystems. They are widely distributed related to their charged molecular structure that provides water solubility. In order to track the fate and behavior of such pollutants, charged dyes with specific absorption in the visible spectra serve as convenient model compounds. We provide a platform of smart adsorbers that efficiently remediate positively and negatively charged dyes (crystal violet and Amaranth) from water. Metal oxide nanoparticles serve as a core with an intrinsically large surface area. The surface potential was tuned towards positive or negative by decorating the cores with self-assembled monolayers of dedicated long-chained phosphonic acid derivatives. Selective remediation of the dyes was obtained with corresponding oppositely charged core-shell nanoparticles. Mixed dye solution can be cleaned by a cascade approach or by applying both particle systems simultaneously. The removal efficiency was determined as a function of particle concentration via UV-spectroscopy. The results of remediation experiments at different pH values and using superparamagnetic iron oxide nanoparticle cores lead to a simple process with recycling capabilit

Tailorable Nanoparticles for Magnetic Water Cleaning of Polychlorinated Biphenyls - Müller, Lukas; Zehetmeier, Anna; Höfling, Anna; Gaß, Henrik; Voß, Johannes; Krappmann, Daniel; Rockmann, Linda; Harrer, Elias; Zahn, Dirk; Hirsch, Andreas; Halik, Marcus (Small Methods, 2025)
Anthropogenic persistent organic pollutants pose a pressing threat to the environment and human health. They can be found in water bodies all around the world at low but hazardous concentrations. Typical representatives of this contaminant class are polychlorinated biphenyls (PCBs). Here, nanoparticulate core-shell water cleaning agents are presented, which are able to remove PCBs of various chlorination degrees from water. The core consists of superparamagnetic iron oxide nanoparticles (SPIONs) providing a large surface area that can be tuned via self-assembled monolayers (SAMs) composed of phosphonic acid derivates. This shell binds the pollutants non-covalently enabling facile magnetic water remediation. By employing positively charged or hydrophobic SAMs different PCBs can be preferentially removed. Furthermore, these orthogonal functionalities can be integrated into one SPION system. By combining charged and hydrophobic phosphonic acid derivates in so-called binary SAMs the removal preference can be convoluted, which works just as well in real river water. The cost-efficient availability of the base materials for these tailorable nanoparticles is complemented with recyclability laying the foundation for a sustainable water cleaning proces
Keywords: persistent organic pollutants; polychlorinated biphenyls; self-assembled monolayers; superparamagnetic iron oxide nanoparticles; tailorable adsorption; water remediation